2002
DOI: 10.1074/jbc.m112355200
|View full text |Cite
|
Sign up to set email alerts
|

Direct Activation of Mitochondrial Apoptosis Machinery by c-Jun N-terminal Kinase in Adult Cardiac Myocytes

Abstract: Although oxidative stress causes activation of c-Jun N-terminal kinase (JNK) and apoptosis in many cell types, how the JNK pathway is connected to the apoptosis pathway is unclear. The molecular mechanism of JNK-mediated apoptosis was investigated in adult rat cardiac myocytes in culture as a model system that is sensitive to oxidative stress. Oxidative stress caused JNK activation, cytochrome c release, and apoptosis without new protein synthesis. Oxidative stress-induced apoptosis was abrogated by dominant n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
221
3
9

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(263 citation statements)
references
References 34 publications
30
221
3
9
Order By: Relevance
“…The effects of Lmna mutations on proteins particularly important for conduction system structure or function might weaken these specialized cells and promote early apoptotic death. Activation of c-jun N-terminal kinase (JNK), a stress-activated protein kinase, has been previously implicated in the process of cardiomyopathy and cardiac conduction system disease by downregulation of the gap junction protein connexin 43 [32,33], and cardiomyocyte apoptosis [34]. However, the present study showed no c-Jun activation in hearts from Lmna +/-mice.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The effects of Lmna mutations on proteins particularly important for conduction system structure or function might weaken these specialized cells and promote early apoptotic death. Activation of c-jun N-terminal kinase (JNK), a stress-activated protein kinase, has been previously implicated in the process of cardiomyopathy and cardiac conduction system disease by downregulation of the gap junction protein connexin 43 [32,33], and cardiomyocyte apoptosis [34]. However, the present study showed no c-Jun activation in hearts from Lmna +/-mice.…”
Section: Discussioncontrasting
confidence: 76%
“…Activation of MAPK signaling cascade has recently been identified in hearts from mice homozygous for the LMNA mutation H222P [23], and this molecular pathway has previously been implicated in the development of cardiomyopathy, conduction defects [32,33] and apoptosis [34].…”
Section: Mitogen-activated Protein Kinase (Mapk) Signaling In the Dismentioning
confidence: 99%
“…In contrast to FAK, PYK2 appears to direct downstream signals to either pro-or anti-apoptotic signaling cascades depending on which molecules bind to the phosphorylated kinase. For instance, Melendez et al (3) previously demonstrated that overexpression of wildtype PYK2 promoted cardiomyocyte apoptosis, perhaps via the preferential activation of JNKs (3,5,6,32) and direct activation of the mitochondrial apoptotic machinery (35). PYK2-dependent apoptosis could be suppressed by prior overexpression of paxillin, which binds to the C-terminal domain of PYK2 (14,36) and prevented JNK activation (3).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these findings, the potent activation of JNK (eightfold) by exogenous ASMase 47 has been reported in primary hepatocytes. Furthermore, the interaction of JNK with mitochondria has been reported during cell death, 48,49 opening the possibility that the role of JNK in hepatic I/R damage may be due to its interaction with mitochondria. However, the cytotoxic role of JNK may be attributable not only to its putative interaction with mitochondria but also to the activation of downstream targets, including BH3-only members of the Bcl-2 family such as Bim, which can be regulated by transcriptional and post-translational mechanisms.…”
Section: Discussionmentioning
confidence: 99%